Feline morbillivirus infection associated with fatal encephalitis in a Bengal cat - Kara L. D. Dawson; Nicole Wildi; Mauro Cavalli; Dennis Rubbenstroth; Anna Oevermann; Torsten Seuberlich (Journal of Veterinary Internal Medicine, 2023)
Abstract Feline morbillivirus (FeMV) is a recently discovered morbillivirus of the family Paramyxoviridae, which include several highly contagious viruses with zoonotic potential. In this case report we describe the detection of FeMV in archived brain tissue of a 2‐month‐old Bengal cat with nonsuppurative encephalitis from the year 2011 in Switzerland by high‐throughput sequencing (HTS). Our metagenomics approach was able to obtain a full‐length sequence covering the entire FeMV genome. Phylogenetic analysis showed that our FeMV strain clustered within FeMV genotype 1. We were able to detect FeMV RNA by in situ hybridization (ISH) in brain sections with inflammatory lesions and demonstrated its potential neurotropism and association with encephalitis. Our results provide further insight into this recently discovered morbillivirus and encourage further investigations into the pathogenesis and epidemiology of associated diseases in cats and potentially other species.